2019
DOI: 10.3390/w11112212
|View full text |Cite
|
Sign up to set email alerts
|

Scour around Piers under Waves: Current Status of Research and Its Future Prospect

Abstract: In this review article, the current status of research on pier scour under waves is presented. This includes a summary of different bridge failure events due to scour, scour mechanism, scour depth predictors under waves, influence of pier shape on scour depth formation, shape of scour hole around piers, and many others. Further, this article describes the scour process, development of scour depth predictors, and the complexity involved in the scour related calculations. Finally, the future scope of research is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The approach employed by the authors constitutes the first attempt to the development of predictive scour models founded more on physical than empirical grounds. A review paper treating the topic of bridge scour under waves can be found at Gazi et al [81], whereas scour at bridge foundations under supercritical flows was recently reviewed by Link et al [82].…”
Section: Physical Modelling and Controlling Scour Parametersmentioning
confidence: 99%
“…The approach employed by the authors constitutes the first attempt to the development of predictive scour models founded more on physical than empirical grounds. A review paper treating the topic of bridge scour under waves can be found at Gazi et al [81], whereas scour at bridge foundations under supercritical flows was recently reviewed by Link et al [82].…”
Section: Physical Modelling and Controlling Scour Parametersmentioning
confidence: 99%
“…On the other hand, the highest relocation of tracers to other CGU types during Flood 2020 was observed from runs (53%). In runs, the the scour hole may also occur (Gazi et al, 2019). Pools can thus act as both a sink and source for bedload by periodically accumulating and releasing waves of sediment during flood flow (Dhont & Ancey, 2018).…”
Section: Influence Of Cgus On Bedload Transportmentioning
confidence: 99%
“…Furthermore, bow-waves can also contribute to the scouring process. A combination of these vortexes eventually lead to scour holes around piers of bridges (Laursen and Toch, 1956;Liu et al 1961;Kwan, 1988;Hosseini et al, 2016), and detailed descriptions on abutment scour depth process are widely available in the literature (e.g., Dey, 1997;Dey and Barbhuiya, 2005;Gazi et al, 2019;Kothyari et al, 1992;Melville and Raudkivi, 1977;Melville and Sutherland, 1988;Moonen and Allegrini, 2015;Namaee and Sui, 2019;Raudkivi and Ettema, 1983).…”
Section: Introductionmentioning
confidence: 99%